Associations Between Socio-Economic Factors and Prevalence of Shigella Infection: An Analysis of Isolated Cases - Rahman, Tajreen; Haque, Md Moynul; Rahman, Mohammad Habibur (Journal of Rangpur Medical College, 2026)
Background: Shigella infection is a major contributor to childhood diarrhoea, particularly in settings where socio-economic and environmental disadvantages limit access to safe water, sanitation, and healthcare. Objective: This study assessed the association between socio-economic factors and Shigella prevalence among isolated paediatric cases. Methods: A hospital-based observational study was conducted from July 2021 to June 2022 in the Paediatrics inpatient department of Sylhet MAG Osmani Medical College Hospital. Ninety-eight children aged ≥6 months with diarrhoea and no recent antibiotic exposure were enrolled. Stool samples underwent culture, biochemical testing, and PCR confirmation.Associations were analysed using SPSS, with significance set at p<0.05. Results: Shigella species were isolated in 13 of 98 children (13.3%), predominantly among those aged 1–5 years and from lower socio-economic backgrounds, although age, gender and socio-economic class showed no significant associations. Conclusion: Shigella infection persists in disadvantaged socio-economic settings, underscoring the need for targeted preventive measures. J Rang Med Col.2026 Mar;11(1): 16-20